2017
DOI: 10.29321/maj.2017.000076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Pelleting and Foliar Nutrition on Growth andYield of Summer Irrigated Sesame (Sesamum indicum L.)

Abstract: Field experiment was conducted during 2017, to investigate the effect of seed pelleting and foliar nutrition on yield and productivity of summer irrigated sesame (Sesamum indicum. L). The experiment was laid out in factorial randomized block design with three replications. The two factors were seed pelleting and foliar nutrition. Pelleted and non pelleted seeds were the two levels of seed pelleting. Foliar nutrition comprised of Urea (1%), DAP (1%), 19:19:19 (NPK) (1%), MnSO 4 (0.5%), MAP (0.5%), Combined nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Govindan and Thirumurugan (2000) observed that the foliar spray of KCl (1 per cent) + KNO 3 (1 per cent) increased the grain yield of green gram by 21.8 per cent. Ramesh and Thirumurugan (2001) stated that foliar applications of 2 per cent DAP and 1 per cent KCl along with benzyladenine 25 ppm had significantly increased the plant height in soybean. The increased lint yield is due to foliar applied potassium under the low soil potassium condition (Cakmak, 2005).…”
Section: Role Of Potassium On Crop Growth and Stress Managementmentioning
confidence: 99%
“…Govindan and Thirumurugan (2000) observed that the foliar spray of KCl (1 per cent) + KNO 3 (1 per cent) increased the grain yield of green gram by 21.8 per cent. Ramesh and Thirumurugan (2001) stated that foliar applications of 2 per cent DAP and 1 per cent KCl along with benzyladenine 25 ppm had significantly increased the plant height in soybean. The increased lint yield is due to foliar applied potassium under the low soil potassium condition (Cakmak, 2005).…”
Section: Role Of Potassium On Crop Growth and Stress Managementmentioning
confidence: 99%
“…Poor fruit set was believed to be one of the significant barriers in capsicum (Saha et al, 2010). Flower and fruit drops can be minimized by applying plant growth regulators in most crops (Chattopadhyay and Sen, 1974) by spraying various growth regulators on foliage (Ramesh and Thirumurugan, 2001).…”
Section: Introductionmentioning
confidence: 99%